A hemostatic material with antibacterial properties and preparation method and application thereof

By combining crosslinked chitosan with rare earth materials, hemostatic materials with excellent water absorption and antibacterial properties are formed, which solves the shortcomings of existing hemostatic materials in major bleeding and antibacterial properties, and achieves more effective hemostatic and antibacterial effects. It is suitable for Emergency wound treatment.

CN116196463BActive Publication Date: 2024-12-17GANJIANG INNOVATION ACAD CHINESE ACAD OF SCI
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310247640.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-15
Publication Date
2024-12-17
Estimated Expiration
2043-03-15

AI Technical Summary

Technical Problem

Existing hemostatic materials have limited hemostatic effects when dealing with major bleeding and lack antibacterial performance, especially in response to emergency situations such as wars and traffic accidents, it is difficult to quickly and effectively control bleeding.

Method used

Cross-linked chitosan is used as the hemostatic material and rare earth materials are used as the only cross-linking agent for chitosan. Coordination between rare earth cations and amino and hydroxyl groups in chitosan is formed to form a larger pore and neat network. The cross-linked chitosan of the structure combines the antibacterial properties of rare earth materials to prepare hemostatic materials with excellent water absorption and antibacterial effects.

Benefits of technology

It improves the water absorption and antibacterial effect of hemostatic materials, enhances its ability to block wounds and absorb blood, significantly improves hemostatic and antibacterial properties, and is suitable for emergency wound dressings. It has a simple process and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116196463B_ABST
    Figure CN116196463B_ABST
Patent Text Reader

Abstract

The present invention provides a hemostatic material with antibacterial properties, a preparation method and an application thereof. The hemostatic material with antibacterial properties comprises cross-linked chitosan, wherein the cross-linking agent is a rare earth material; the rare earth material comprises rare earth salts; wherein the cations in the rare earth salts comprise cerium ions and / or europium ions. In the cross-linked chitosan, the chitosan has a certain viscosity and good adsorption, and has the ability to seal wounds and adsorb exuded blood; the rare earth material has excellent antibacterial properties. The hemostatic material with antibacterial properties obtained by combining the two has large pores and neat arrangement, strong water absorption, low hemolysis rate, and is more fully adhered to the skin of the affected area when used, and thus the cross-linked chitosan has excellent hemostatic and antibacterial effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of materials, and in particular relates to a hemostatic material with antibacterial properties, a preparation method and an application thereof. Background Art

[0002] Blood plays an important role in the human body, such as transportation, maintaining body balance, and supporting immune system function. Excessive bleeding can cause illness or even death. According to statistics, more than 18% of deaths from war trauma can be avoided through timely treatment; in traffic accidents, there is a long time from injury to hospital, which makes patients prone to death due to lack of timely rescue. Effective and rapid hemostasis can increase the survival rate by 40%. Uncontrollable bleeding is an important cause of death in wars, traffic accidents, natural disasters and other scenarios.

[0003] Chitosan has the advantages of wide sources, economy, good biocompatibility, biodegradability, and antibacterial properties. It has become one of the most widely used hemostatic materials. However, the hemostatic effect of single-component chitosan hemostatic materials is average, especially when dealing with heavy bleeding, its role is only equivalent to gauze, and its antibacterial activity only exists in solution state.

[0004] The molecular chain of chitosan has multiple repeating units, and the C-3 and C-6 hydroxyl groups and the C-2 amino group of each repeating unit are active. Therefore, new wound dressings can be developed by modifying chitosan. The cross-linked chitosan sponge prepared by Zou Shengcan et al. has a water absorption rate of up to 28.4 times, which is more than twice that of ordinary chitosan dressings, but the liquid absorption performance is still low and the antibacterial performance is poor. The hydrogen bond self-assembled chitosan hemostatic sponge prepared by Wang Xiaochen et al. has a liquid absorption rate of up to 50 times, but its antibacterial property is poor.

[0005] CN102008751A relates to a biodegradable stent composite material and a preparation method thereof. The biodegradable material has a multi-gradient composite structure, including: a matrix composed of medical metal or its alloy; a chemical coupling layer attached to the surface of the matrix; a polymer transition layer attached to the surface of the chemical coupling layer; and a degradable polymer functional layer fixed to the surface of the polymer transition layer. The stent composite material disclosed in the invention has excellent mechanical properties, degradation properties and biocompatibility, and can also absorb and carry the required therapeutic drugs to meet the needs of clinical treatment.

[0006] CN103695654A discloses a method for recovering rare earth from a low-concentration rare earth solution using loaded chitosan, comprising the following steps: (1) dissolving chitosan powder in an acetic acid solution, adjusting the pH to 5.8, and obtaining a chitosan solution; (2) adding an appropriate amount of distilled water to the chitosan solution and an inorganic carrier in a mass ratio of 1:4, uniformly mixing, drying, and grinding to obtain loaded chitosan; (3) adding the loaded chitosan to the rare earth solution in a mass ratio of 1:1 to the rare earth ions in the rare earth solution, and adsorbing by oscillation for 60 minutes at 25°C, pH 3; (4) analyzing the loaded chitosan adsorbed with rare earth ions in step (3) with a dilute acid solution, wherein the concentration of the analyzed dilute acid solution is 1 to 5 mol / L, and recovering the rare earth from the obtained rare earth analyzed solution by a precipitation method. The invention can achieve an adsorption rate of more than 95% for rare earth ions lanthanum, yttrium and gadolinium, has a high resolution rate, good regeneration performance, high rare earth recovery rate, and is pollution-free to the environment. It can be used to treat low-concentration rare earth wastewater.

[0007] Therefore, it is of great significance to develop new antibacterial hemostatic materials that are fast, safe and cheap. Summary of the invention

[0008] In view of the deficiencies of the prior art, the object of the present invention is to provide a hemostatic material with antibacterial properties and a preparation method and application thereof.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a hemostatic material with antibacterial properties, wherein the hemostatic material with antibacterial properties comprises cross-linked chitosan, wherein the cross-linking agent is a rare earth material; the rare earth material comprises rare earth salts; wherein the cations in the rare earth salts comprise cerium ions and / or europium ions.

[0011] The present invention creatively proposes a hemostatic material with antibacterial properties, wherein the hemostatic material comprises cross-linked chitosan, wherein a rare earth material is used as the only cross-linking agent of chitosan, and coordination occurs between the rare earth material cation and the amino group and the hydroxyl group in the chitosan to achieve the effect of cross-linking the chitosan. The SEM results show that ( Figure 1 , 2 ), cross-linked chitosan has larger pores and a more orderly network structure than chitosan.

[0012] In cross-linked chitosan, chitosan has a certain viscosity and good adsorption, and has the ability to seal wounds and absorb exuded blood; rare earth materials have excellent antibacterial properties. The hemostatic material with antibacterial properties prepared by combining the two has large pores and neat arrangement, strong water absorption and low hemolysis rate, and can fit more fully with the skin of the affected area when used, so the hemostatic material has excellent hemostatic and antibacterial effects.

[0013] Preferably, the molecular weight of the chitosan is in the range of 50,000 to 300,000;

[0014] The specific value of 50,000-300,000 can be 50,000, 100,000, 150,000, 200,000, 250,000 or 300,000, etc.;

[0015] Other specific point values ​​within the above numerical ranges can be selected and will not be described in detail here.

[0016] Preferably, the deacetylation degree of the chitosan is 75-95%.

[0017] The specific value of 75-95% may be 75%, 78%, 81%, 84%, 87%, 90%, 93% or 95% etc.;

[0018] Other specific point values ​​within the above numerical ranges can be selected and will not be described in detail here.

[0019] Preferably, the cations in the rare earth salts include cerium ions.

[0020] The cations in the rare earth salts involved in the present invention specifically include cerium ions, and the hemostatic material with antibacterial properties is better in water absorption, antibacterial properties and hemostatic effect.

[0021] Preferably, the cations in the rare earth salts also include any one of lanthanum ions, yttrium ions, terbium ions, neodymium ions, gadolinium ions, praseodymium ions, samarium ions, erbium ions or dysprosium ions, or a combination of at least two of them. The combination of at least two includes a combination of lanthanum ions and yttrium ions, a combination of yttrium ions and terbium ions, or a combination of neodymium ions and gadolinium ions, and any other combinations can be selected and will not be described here one by one.

[0022] Preferably, the cations in the rare earth salts also include any one of lanthanum ions, yttrium ions or terbium ions, or a combination of at least two of them; the combination of at least two includes a combination of lanthanum ions and yttrium ions, a combination of yttrium ions and terbium ions, or a combination of lanthanum ions and terbium ions, and any other combinations can be selected and will not be described in detail here.

[0023] Preferably, the anions in the rare earth salts include nitrate ions and / or chloride ions.

[0024] Preferably, the anions in the rare earth salts are nitrate ions.

[0025] Preferably, the rare earth material further includes rare earth oxide.

[0026] Preferably, the rare earth oxide includes any one of cerium dioxide, lanthanum oxide, yttrium oxide, terbium oxide, europium oxide or gadolinium oxide, or a combination of at least two of them. The combination of at least two includes a combination of cerium dioxide and lanthanum oxide, a combination of lanthanum oxide and yttrium oxide, or a combination of europium oxide and gadolinium oxide, and any other combinations can be selected and will not be described here one by one.

[0027] Preferably, the rare earth oxide comprises ceria.

[0028] Preferably, the mass ratio of the cross-linking agent to chitosan is 1:(7.5-100);

[0029] The specific value in (7.5-100) can be 7.5, 10, 20, 30, 40, 50, 60, 70, 80, 90 or 100, etc.;

[0030] Other specific point values ​​within the above numerical ranges can be selected and will not be described in detail here.

[0031] Preferably, the mass ratio of the cross-linking agent to chitosan is 1:(12-50).

[0032] The specific value in (12-50) can be 12, 15, 20, 25, 30, 40, 45 or 50, etc.;

[0033] Other specific point values ​​within the above numerical ranges can be selected and will not be described in detail here.

[0034] When the mass ratio of the cross-linking agent to chitosan of the present invention is 1:(7.5-100), the antibacterial ability and coagulation performance of the hemostatic material with antibacterial properties are stronger. When the mass ratio of the cross-linking agent to chitosan is reduced to 1:(12-50), the antibacterial and hemostatic abilities of the hemostatic material are further improved.

[0035] In a second aspect, the present invention provides a method for preparing the hemostatic material with antibacterial properties as described in the first aspect, the preparation method comprising the following steps:

[0036] The cross-linking agent solution and chitosan are mixed, the mixed solution is stirred until completely dissolved, the pH value is adjusted to 3-11, the mixture is allowed to stand, centrifuged, washed, and vacuum-freeze-dried to obtain the hemostatic material with antibacterial properties.

[0037] The hemostatic material with antibacterial properties of the present invention can be prepared by mixing the crosslinking agent solution and chitosan, adjusting the pH, standing, centrifuging, washing, and vacuum freeze-drying. The preparation method of the present invention is simple in process and suitable for industrial scale-up.

[0038] Preferably, the method for preparing the crosslinker solution comprises:

[0039] The cross-linking agent is immersed in a 0.5-3% acetic acid aqueous solution for 8-16 hours to obtain the cross-linking agent solution.

[0040] The specific value of 0.5-3% can be selected from 0.5%, 1%, 1.5%, 2%, 2.5% or 3% etc.;

[0041] The specific value of 8-16h can be 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h or 16h, etc.;

[0042] Other specific point values ​​within the above numerical ranges can be selected and will not be described in detail here.

[0043] Preferably, the stirring speed is 500-700 rpm.

[0044] The specific value of 500-700rpm can be selected from 500rpm, 550rpm, 600rpm, 650rpm or 700rpm, etc.;

[0045] Other specific point values ​​within the above numerical ranges can be selected and will not be described in detail here.

[0046] Preferably, the adjusted pH is 6-8; more preferably, the adjusted pH is 6.5-7.5.

[0047] The specific values ​​in 6-8 can be 6, 6.3, 6.6, 6.9, 7.2, 7.5, 7.7 or 8, etc.;

[0048] The specific value of 6.5-7.5 can be 6.5, 6.6, 6.7, 6.8, 6.9, 7, 7.1, 7.2, 7.3, 7.4 or 7.5, etc.;

[0049] Other specific point values ​​within the above numerical ranges can be selected and will not be described in detail here.

[0050] After the crosslinking agent solution of the present invention is mixed with chitosan, when the pH is adjusted to 6-8, the obtained hemostatic material has a more orderly network structure, and has stronger antibacterial and hemostatic effects. When the pH is further reduced to 6.5-7.5, the antibacterial and hemostatic effects of the hemostatic material are further improved.

[0051] Preferably, the concentration of chitosan in the mixed solution is 0.5-3wt%.

[0052] The specific value of 0.5-3wt% can be selected from 0.5wt%, 0.8wt%, 1.1wt%, 1.4wt%, 1.7wt%, 2wt%, 2.3wt%, 2.6wt%, 2.9wt% or 3wt%, etc.;

[0053] Other specific point values ​​within the above numerical ranges can be selected and will not be described in detail here.

[0054] Preferably, the standing time is 4-10h;

[0055] The specific value of 4-10h can be 4h, 5h, 6h, 7h, 8h, 9h or 10h, etc.;

[0056] Other specific point values ​​within the above numerical ranges can be selected and will not be described in detail here.

[0057] Preferably, the centrifugation time is 2-10 min;

[0058] The specific value of 2-10min can be 2min, 3min, 4min, 5min, 6min, 7min, 8min, 9min or 10min, etc.;

[0059] Other specific point values ​​within the above numerical ranges can be selected and will not be described in detail here.

[0060] Preferably, the centrifugal speed is 100-8000rpm;

[0061] The specific value of 100-8000rpm can be selected from 100rpm, 1000rpm, 2000rpm, 3000rpm, 4000rpm, 5000rpm, 6000rpm, 7000rpm or 8000rpm, etc.;

[0062] Other specific point values ​​within the above numerical ranges can be selected and will not be described in detail here.

[0063] Preferably, the washing liquid is water and / or anhydrous ethanol.

[0064] Preferably, the vacuum freeze-drying time is 20-30 hours.

[0065] The specific value of 20-30h can be selected from 20h, 22h, 24h, 26h, 28h or 30h, etc.;

[0066] Other specific point values ​​within the above numerical ranges can be selected and will not be described in detail here.

[0067] In a third aspect, the present invention provides use of the hemostatic material with antibacterial properties as described in the first aspect or the preparation method as described in the second aspect in the preparation of a wound care product.

[0068] Compared with the prior art, the present invention has the following beneficial effects:

[0069] 1. The present invention creatively proposes a hemostatic material with antibacterial properties, wherein the hemostatic material comprises cross-linked chitosan, wherein a rare earth material is used as the only cross-linking agent of chitosan, and coordination occurs between the rare earth material cation and the amino group and hydroxyl group in chitosan to achieve the effect of cross-linking chitosan. SEM results show that ( Figure 1 , 2 ), cross-linked chitosan has larger pores and a more orderly network structure than chitosan.

[0070] In cross-linked chitosan, chitosan has a certain viscosity and good adsorption, and has the ability to seal wounds and absorb exuded blood; rare earth materials have excellent antibacterial properties. The hemostatic material with antibacterial properties prepared by combining the two has large pores and neat arrangement, strong water absorption and low hemolysis rate, and can fit more fully with the skin of the affected area when used, so the hemostatic material has excellent hemostatic and antibacterial effects.

[0071] 2. The hemostatic material with antibacterial properties of the present invention can be prepared by mixing the crosslinking agent solution and chitosan, adjusting the pH, standing, centrifuging, washing, and vacuum freeze-drying. The preparation method of the present invention is simple and suitable for industrial scale-up. BRIEF DESCRIPTION OF THE DRAWINGS

[0072] Figure 1 This is the SEM characterization result of the material obtained in Example 1.

[0073] Figure 2 This is the SEM characterization result of the material obtained in Comparative Example 1.

[0074] Figure 3 These are the antibacterial performance test results of the materials prepared in Example 1 and Comparative Example 1, wherein A corresponds to the antibacterial performance evaluation result of Escherichia coli in Example 1, B corresponds to the antibacterial performance evaluation result of Escherichia coli in Comparative Example 1, C corresponds to the antibacterial performance evaluation result of Staphylococcus aureus in Example 1, and D corresponds to the antibacterial performance evaluation result of Staphylococcus aureus in Comparative Example 1. DETAILED DESCRIPTION

[0075] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0076] The process, conditions, reagents, experimental methods, etc. for implementing the present invention, except for the contents specifically mentioned below, are all common knowledge and common common sense in the art, and the present invention has no particular restrictions. The experimental methods without specifying specific conditions in the embodiments are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0077] Unless otherwise specified, all technical terms and scientific terms used in this specification have the same meaning as those generally understood by those skilled in the art to which the present invention belongs. However, in case of any conflict, the present specification including the definitions shall prevail.

[0078] Example 1

[0079] This embodiment provides a hemostatic material with antibacterial properties, and the preparation method of the hemostatic material is as follows:

[0080] 1 part of cerium nitrate was dissolved in 1% acetic acid aqueous solution and soaked for 8 hours, and the concentration of rare earth material in the solution was 4wt%; then 20 parts of chitosan (80,000 molecular weight, deacetylation degree of 90%) and acetic acid aqueous solution were added, and the concentration of chitosan in the acetic acid aqueous solution was adjusted to 2wt%, and stirred at a stirring speed of 600rpm for 6 hours, at which time the chitosan was completely dissolved; the pH was adjusted to 7 with sodium hydroxide, and the mixture was allowed to stand for 6 hours, and then centrifuged at 8000rpm for 5 minutes, and the precipitate was washed twice with deionized water; then vacuum freeze-dried for 30 hours to obtain the hemostatic material with antibacterial properties (the SEM characterization of the material is as shown in FIG. Figure 1 shown).

[0081] Example 2

[0082] This embodiment provides a hemostatic material with antibacterial properties, and the preparation method of the hemostatic material is as follows:

[0083] One part of cerium nitrate is dissolved in a 0.5% acetic acid aqueous solution and soaked for 16 hours, and the concentration of rare earth materials in the solution is 4wt%; then, 12 parts of chitosan (80,000 molecular weight, 95% deacetylation degree) and acetic acid aqueous solution are added, and the concentration of chitosan in the acetic acid aqueous solution is adjusted to 3wt%, and stirred at a stirring speed of 700rpm for 5 hours, at which time the chitosan is completely dissolved; sodium hydroxide is used to adjust the pH to 6.5, and the mixture is allowed to stand for 10 hours, and then centrifuged at 8000rpm for 5 minutes, and the precipitate is washed twice with deionized water; then vacuum freeze-dried for 30 hours to obtain the hemostatic material with antibacterial properties.

[0084] Example 3

[0085] This embodiment provides a hemostatic material with antibacterial properties, and the preparation method of the hemostatic material is as follows:

[0086] Dissolve 1 part of cerium nitrate in 3% acetic acid aqueous solution and soak for 8 hours, the concentration of rare earth material in the solution is 4wt%; then add 18 parts of chitosan (300,000 molecular weight, deacetylation degree of 95%) and acetic acid aqueous solution, adjust the concentration of chitosan in the acetic acid aqueous solution to 0.5wt%, stir at a stirring speed of 500rpm for 7 hours, at which time the chitosan is completely dissolved; use sodium hydroxide to adjust the pH to 7.5, let stand for 4 hours, then centrifuge at 8000rpm for 5min, wash the precipitate twice with deionized water; then use vacuum freeze-drying for 30 hours to obtain the hemostatic material with antibacterial properties.

[0087] Example 4

[0088] This embodiment provides a hemostatic material with antibacterial properties. The preparation method of the hemostatic material is different from that of Example 1 only in that the preparation raw material does not contain cerium nitrate, and the cerium nitrate is replaced by europium nitrate in an equal molar amount. The rest is the same as that of Example 1.

[0089] Example 5

[0090] This embodiment provides a hemostatic material with antibacterial properties. The preparation method of the hemostatic material is different from that of Example 1 only in that the preparation raw material does not contain cerium nitrate, and the cerium nitrate is replaced by lanthanum nitrate in an equal molar amount. The rest is the same as Example 1.

[0091] Example 6

[0092] This embodiment provides a hemostatic material with antibacterial properties. The preparation method of the hemostatic material is different from that of Example 1 only in that the preparation raw material does not contain cerium nitrate, and the cerium nitrate is replaced by yttrium nitrate in an equal molar amount. The rest is the same as Example 1.

[0093] Example 7

[0094] This embodiment provides a hemostatic material with antibacterial properties. The preparation method of the hemostatic material is different from that of Example 1 only in that the preparation raw material does not contain cerium nitrate, and the cerium nitrate is replaced by terbium nitrate in an equal molar amount. The rest is the same as that of Example 1.

[0095] Example 8

[0096] This embodiment provides a hemostatic material with antibacterial properties. The preparation method of the hemostatic material is different from that of Example 1 only in that the preparation raw material does not contain cerium nitrate, and the cerium nitrate is replaced by cerium dioxide in an equal molar amount. The rest is the same as Example 1.

[0097] Example 9

[0098] This embodiment provides a hemostatic material with antibacterial properties. The preparation method of the hemostatic material is different from that of Example 1 only in that 20 parts of chitosan are replaced by 10 parts of chitosan in the preparation raw materials, and the rest is the same as Example 1.

[0099] Example 10

[0100] This embodiment provides a hemostatic material with antibacterial properties. The preparation method of the hemostatic material is different from that of Example 1 only in that 20 parts of chitosan are replaced by 55 parts of chitosan in the preparation raw materials, and the rest is the same as Example 1.

[0101] Embodiment 11

[0102] This embodiment provides a hemostatic material with antibacterial properties. The preparation method of the hemostatic material is different from that of Example 1 only in that the pH is adjusted to 6.5 using sodium hydroxide instead of using sodium hydroxide to adjust the pH to 6 in the preparation raw materials, and the rest is the same as Example 1.

[0103] Example 12

[0104] This embodiment provides a hemostatic material with antibacterial properties. The preparation method of the hemostatic material is different from that of Example 1 only in that the pH is adjusted to 8 using sodium hydroxide instead of using sodium hydroxide to adjust the pH to 6.5 in the preparation raw materials, and the rest is the same as Example 1.

[0105] Comparative Example 1

[0106] This comparative example provides a chitosan material. The preparation method of the chitosan material is different from that of Example 1 in that no rare earth material is added. The specific preparation method is as follows:

[0107] The 1% acetic acid aqueous solution was allowed to stand for 8 hours, and then 20 parts of chitosan (molecular weight of 80,000, deacetylation degree of 90%) were added, and the concentration of chitosan in the acetic acid aqueous solution was adjusted to 2wt%, and stirred at a stirring speed of 600rpm for 6 hours, at which time the chitosan was completely dissolved; the pH was adjusted to 7 with sodium hydroxide, and the solution was allowed to stand for 6 hours, and then centrifuged at 8000rpm for 5 minutes, and the precipitate was washed twice with deionized water; and then vacuum freeze-dried for 30 hours to obtain the chitosan material (the SEM characterization of the material is as shown in FIG. Figure 2 shown).

[0108] Test Example 1

[0109] This test example evaluates the antibacterial effect of the materials prepared in the examples or comparative examples, and the specific evaluation method is:

[0110] According to the method in GB / T 20944.3-2008, Evaluation of antibacterial properties of textiles Part 3: Oscillation method, the antibacterial rate is calculated as follows: Y = (Wt-Qt) / Wt×100%. The results are shown in Table 1. Figure 3 As shown;

[0111] Wherein Y is the antibacterial rate of the hemostatic material with antibacterial properties, Wt is the average value (CFU / mL) of the live bacteria concentration in the flask after 18 hours of oscillation contact of the chitosan material prepared in Comparative Example 1, and Qt is the average value (CFU / mL) of the live bacteria concentration in the flask after 18 hours of oscillation contact in each example.

[0112] Table 1

[0113]

[0114]

[0115] It can be seen from the data in Table 1 that the antibacterial rates of the hemostatic material with antibacterial properties prepared in Example 1 against Staphylococcus aureus and Escherichia coli are both over 99%.

[0116] In Examples 4-8, cerium nitrate was replaced by europium nitrate, lanthanum nitrate, yttrium nitrate, terbium nitrate and cerium dioxide, respectively, and the antibacterial rates thereof were all lower than those in Example 1, indicating that the material obtained by selecting the rare earth element cerium has a stronger antibacterial effect.

[0117] Compared with Example 1, the mass ratio of the cross-linking agent to chitosan in Example 9 and Example 10 is not within the preferred range of 1:(12-50), and the antibacterial rates are lower than that in Example 1, indicating that when the mass ratio of the cross-linking agent to chitosan is within the preferred range of 1:(12-50), the hemostatic material with antibacterial properties has a stronger antibacterial effect.

[0118] Compared with Example 1, the pH of Example 11 and Example 12 is not within the preferred range of 6.5-7.5, and the antibacterial rates of both are lower than that of Example 1, indicating that when the pH is preferably 6.5-7.5, the hemostatic material with antibacterial properties has a better antibacterial effect.

[0119] The antibacterial rates of all groups of examples are greater than 0, indicating that compared with the comparative example 1 using only chitosan, the materials prepared by combining chitosan with rare earth elements in each example have more significant antibacterial effects.

[0120] Test Example 2

[0121] This test example evaluates the hemostatic effect of the materials prepared in the examples or comparative examples, and the specific evaluation method is:

[0122] The coagulation BCI index test method is:

[0123] Accurately weigh 10 mg of the sample to be tested in each embodiment or comparative example, place in a 37°C water bath for 5 min, then gently drip 0.1 mL of blood (fresh anticoagulated rabbit blood product purchased from Yuanye Biology) on the sample, then immediately drip 20 μL of 0.2M CaCl2 solution, slowly add 25 mL of deionized water to the beaker after 5 min, shake at 50 rpm for 5 min at 37°C, then take out the solution, and measure the absorbance Abs value at 545 nm with an ultraviolet spectrophotometer wavelength. The control group does not add the sample to be tested, directly add 0.1 mL of blood to the beaker, then add 25 mL of deionized water to measure the Abs value at the same wavelength, and then calculate the coagulation index BCI of each group, and the calculation formula is: BCI=(absorbance value of each embodiment or comparative group / absorbance value of the control group)×100%, and the results are shown in Table 2.

[0124] The hemolysis rate test method is:

[0125] The hemolysis rate was detected by immunoturbidimetric method with reference to GB / T 16886.4-2003 / ISO 10993-4:2002, Biological evaluation of medical devices Part 4: Selection of tests for interaction with blood. The results are shown in Table 2.

[0126] Table 2

[0127]

[0128]

[0129] It can be seen from the data in Table 2 that the hemolysis rate of the materials prepared in each embodiment is less than 5%, which meets the requirements for use of medical devices.

[0130] Examples 4-8 replace cerium nitrate with europium nitrate, lanthanum nitrate, yttrium nitrate, terbium nitrate and cerium dioxide respectively, and their BCIs are all higher than that of Example 1, indicating that the material made by selecting the rare earth element cerium has a stronger hemostatic effect.

[0131] Compared with Example 1, the mass ratio of the cross-linker to chitosan in Example 9 and Example 10 is not within the preferred range of 1:(12-50), and the BCI is higher than that in Example 1, indicating that when the mass ratio of the cross-linker to chitosan is within the preferred range of 1:(12-50), the hemostatic property of the hemostatic material with antibacterial properties is better.

[0132] Compared with Example 1, the pH of Example 11 and Example 12 is not within the preferred range of 6.5-7.5, and the BCI of both Examples 11 and 12 is higher than that of Example 1, indicating that when the pH is preferably 6.5-7.5, the hemostatic effect of the hemostatic material with antibacterial properties is good.

[0133] Compared with Example 1, the raw materials of Comparative Example 1 do not contain rare earth elements, and its BCI is higher than that of Example 1, indicating that the hemostatic effect of the material prepared by using chitosan and rare earth elements in combination is stronger.

[0134] Test Example 3

[0135] The moisturizing effect of the materials obtained in the examples or comparative examples of this test example was evaluated, and the specific evaluation method was the test of the liquid absorption multiple:

[0136] The hemostatic material with antibacterial properties prepared in each embodiment or comparative example is cut into small pieces of sponge of 1 cm×1 cm, weighed and recorded as m0, placed in PBS buffer and soaked for 30 seconds, then clamped at one end with tweezers and gently lifted out, naturally drained for 60 seconds and weighed, recorded as m1, accurately weighed to 1 mg, and then the liquid absorption rate was calculated, liquid absorption rate = (m1-m0) / m0×100%, the results are shown in Table 3.

[0137] Table 3

[0138] Group Liquid absorption rate (%) Example 1 5430 Example 2 5245 Example 3 5134 Example 4 4679 Example 5 4303 Example 6 4188 Example 7 3547 Example 8 3252 Example 9 3123 Example 10 3208 Embodiment 11 3235 Example 12 1602 Comparative Example 1 1782

[0139] It can be seen from the data in Table 3 that the liquid absorption rates of Examples 1-3 are all over 5000%, which is significantly higher than that of Comparative Example 1, indicating that the use of rare earth elements to cross-link chitosan on the basis of chitosan can effectively enhance the hygroscopicity of the prepared material. Materials with good hygroscopicity fit more closely to the skin, which in turn affects the coagulation and antibacterial properties of the material.

[0140] In Examples 4-8, cerium nitrate is replaced by europium nitrate, lanthanum nitrate, yttrium nitrate, terbium nitrate and cerium dioxide, respectively, and the liquid absorption rates thereof are all lower than that of Example 1, indicating that the material made by selecting the rare earth element cerium has a stronger moisture absorption effect.

[0141] Compared with Example 1, the mass ratio of the cross-linking agent to chitosan in Example 9 and Example 10 is not within the preferred range of 1:(12-50), and the liquid absorption rate is lower than that in Example 1, indicating that when the mass ratio of the cross-linking agent to chitosan is within the preferred range of 1:(12-50), the hygroscopicity of the hemostatic material with antibacterial properties is better.

[0142] Compared with Example 1, the pH of Example 11 and Example 12 is not within the preferred range of 6.5-7.5, and the liquid absorption rates of both are lower than that of Example 1, indicating that when the pH is preferably 6.5-7.5, the hemostatic material with antibacterial properties has a good moisture absorption effect.

[0143] The applicant declares that the present invention illustrates the preparation process of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

[0144] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0145] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

Claims

1. A hemostatic material with antibacterial properties, characterized in that: The hemostatic material with antibacterial properties comprises cross-linked chitosan, wherein the cross-linking agent is cerium nitrate; The molecular weight of the chitosan is in the range of 50,000 to 300,000; the deacetylation degree of the chitosan is 75 to 95%; The mass ratio of the cross-linking agent to chitosan is 1:(12-50); The hemostatic material with antibacterial properties is prepared by the following method, which comprises the following steps: mixing a crosslinking agent solution and chitosan, stirring until the chitosan is completely dissolved to obtain a mixed solution, adjusting the pH to 6.5-7.5, standing, centrifuging, washing, and vacuum freeze-drying to obtain the hemostatic material with antibacterial properties; The concentration of chitosan in the mixed solution is 0.5-3wt%; The preparation method of the cross-linking agent solution comprises: soaking the cross-linking agent in a 0.5-3% acetic acid aqueous solution for 8-16 hours to obtain the cross-linking agent solution.

2. The method for preparing the hemostatic material with antibacterial properties according to claim 1, characterized in that: The preparation method comprises the following steps: Mixing the crosslinking agent solution and chitosan, stirring until the chitosan is completely dissolved to obtain a mixed solution, adjusting the pH to 6.5-7.5, standing, centrifuging, washing, and vacuum freeze-drying to obtain the hemostatic material with antibacterial properties; The concentration of chitosan in the mixed solution is 0.5-3wt%; The preparation method of the cross-linking agent solution comprises: soaking the cross-linking agent in a 0.5-3% acetic acid aqueous solution for 8-16 hours to obtain the cross-linking agent solution.

3. The method for preparing the hemostatic material with antibacterial properties according to claim 2, characterized in that: The stirring speed is 500-700 rpm.

4. The method for preparing the hemostatic material with antibacterial properties according to claim 2, characterized in that: The standing time is 4-10 hours.

5. The method for preparing the hemostatic material with antibacterial properties according to claim 2, characterized in that: The centrifugation time is 2-10 min.

6. The method for preparing the hemostatic material with antibacterial properties according to claim 2, characterized in that: The centrifugal speed is 100-8000 rpm.

7. The method for preparing the hemostatic material with antibacterial properties according to claim 2, characterized in that: The washing liquid is water and / or anhydrous ethanol.

8. The method for preparing the hemostatic material with antibacterial properties according to claim 2, characterized in that: The vacuum freeze drying time is 20-30h.

9. Use of the hemostatic material with antibacterial properties according to claim 1 or the preparation method according to any one of claims 2 to 8 in the preparation of wound care products.

Citation Information

Patent Citations

  • Biodegradable stent composite material and preparation method thereof

    CN102008751A

  • Method for recovering rare earth from low-concentration rare-earth solution by using loaded chitosan

    CN103695654A

  • Biofilms of rare-earth element contained chitosan and / or derivatives of chitosan

    CN102492182A

  • Biological sponge with rare-earth composite of chitosan and / or derivatives of chitosan

    CN102492183A

  • Preparation method of biodegradable wound dressing

    CN109260501A